Low expression and Hypermethylation of ATP2B1 in Intrahepatic Cholangiocarcinoma Correlated With Cold Tumor Microenvironment - Zhang, Xiehua; He, Yuchao; Ren, Peiqi; Chen, Lu; Han, Zhiqiang; Qi, Lisha; Chen, Liwei; Luo, Yi; Zhang, Ning; Lu, Wei; Guo, Hua (Frontiers in Oncology, 2022)
Background The efficacy of current therapeutic schedule is limited owing to fibroproliferative tumor microenvironment (TME) of cholangiocarcinoma, compelling a search for new therapeutic targets. Methods Gene expression profiles and methylation profiles were obtained from UCSC Xena. Consensus clustering was performed on the transcriptome data of cholangiocarcinoma to determine the different immune subtypes. The differentially expressed genes (DEGs) between hot tumor and cold tumors were identified. ESTIMATE was used to assess immune score, and the cases were separated into relatively superior and inferior immune score groups. Single-sample gene set enrichment analysis was applied to assess 28 immune cells in the cholangiocarcinoma microenvironment. Unsupervised consensus was applied for methylation profiling to distribute the high and low methylation groups. The correlation between DNA methylation and mRNA expression was investigated, and the relationship between the ATP2B1 gene and the immune microenvironment was explored. Finally, 77 cases of intrahepatic cholangiocarcinoma (ICC) were collected for verification. Results Seven subtypes were related to patient outcomes (P=0.005). The proportions of CD8+ T cells in the “hot” immune type was significantly greater than that in the “cold” immune type (P<0.05). Next, DEGs and DNA methylation-governed genes were intersected, and ATP2B1 was identified as a prognosis factor in ICC (P=0.035). ATP2B1 expression was positively correlated with immune scores (P=0.005, r=0.458), the levels of infiltrating CD8+ T cells (P=0.004, r=0.47), and CD4+ T cells (P=0.027, r=0.37). Immunohistochemistry confirmed that the amounts of CD8+ and CD4+ T cells were significantly higher in ICC tissue samples than in tissues with ATP2B1 overexpression (P<0.05). Conclusions ATP2B1 overexpression can activate immune signals and prompt cold tumor response.